Samorządność gminna i jej gwarancje w Rzeczypospolitej Polskiej i w kraju związkowym Brandenburgia - Behr, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The subject of this article is the commune in the Republic of Poland and in the Brandenburg Land. A commune is a part of public administration which is based on decentralization. The legal construction of this basic entity of local government was created in view of its self-governance. The main methodology used in this work is based on the textual analysis of legal acts. The aim of the following work is to explain the conceptual meaning of communal self-governance in the aforementioned states and to analyze the comparability range of its concept. In the Brandenburg Land the concept of communal self-governance is built on the basis of self-governance guaranties. These guaranties are analyzed in detail. While in the Brandenburg Land the catalogue of these guaranties is well-known and acceptable, in the Republic of Poland it is still unclear. In order to arrange this issue, a comparable classification of self-governance guaranties in the Republic of Poland was proposed.
Keywords: Rzeczpospolita Polska; Brandenburgia (land); samorząd gminny; samorządność